THE IMPACT OF RISKS ON ENSURING FINANCIAL STABILITY OF SMALL BUSINESS ENTERPRISES AND WAYS OF THEIR MANAGEMENT (International Congress on Economics, Management and Business Studies, 2026)
This thesis provides a comprehensive scientific study of the impact of economic and financial risks on ensuring the financial stability of small business enterprises, as well as mechanisms for their effective management. In modern economic conditions, small business entities play a crucial role as an important component of the national economy by ensuring economic growth, creating new jobs, forming a competitive environment, and increasing population income. At the same time, global economic instability, inflation processes, changes in financial markets, rising costs of credit resources, and external economic factors significantly affect the financial stability of small businesses.
Keywords: diversification, insurance, financial monitoring, credit portfolio optimization, digital technologies